Bioefficacy of some indigenous products in the management of okra fruit borers (The Journal of Plant Protection Sciences, 2020)
A field experiment was conducted in kharif, 2003 at Main Agricultural Research Station, University of Agricultural Sciences, Dharwad to evaluate the bioefficacy of some indigenous products against okra fruit borers, Earias vittella Fabricius and Helicoverpa armigera Hubner. Different indigenous products like NSKE (5%), GCKE, sweet flag extract (5%), garlic extract (5%), cow dung (10%) and cow urine (10%) were tried individually and in combinations along with endosulfan (0.07%) and untreated control. Repeated sprays of GCKE recorded least number of eggs (1.40 eggs/plant) followed by NSKE (5%) alternated with cow dung 10 per cent (1.71 eggs and cow urine used individually were not effective against the borers and recorded higher fruit damage of 55.70 and 52.10 per cent, respectively. GCKE was significantly superior in reducing the fruit borer damage to the tune of 64.83 per cent with higherbenefit: cost ratio was noticed in endosulfan treatment (15.00) followed by treatment involving NSKE alternated with cow urine 10% (13.00), repeated sprays of GCKE (10) and NSKE alternated with cowdung 10% (7.90).
Keywords: Abelmoschus; armigera; untreated